Initial Need Analysis of Applied English for Students of English Study Program in the Hospitality Field - Nastiti, Intan Aulia; Noviabahari, Jannatul Laily; Prakosha, Donni (PAEDAGOGIA, 2026)
In the field of vocational hospitality education, English instruction is often not fully suited to the specific communication requirements of workplace interaction, especially for students with primary languages preparing for hospitality careers. Although previous ESP needs analyses focused primarily on hospitality or tourism courses, limited research has examined the corresponding English needs of English-based students in vocational polytechnics. The study aims to identify the priority language skills, the context of work place communication, learning preferences and perceived constraints of these students. Data collected from 50 students were analyzed using descriptive quantitative survey designs and frequency and percentage distributions. The results indicate that students prioritize speaking and listening skills for guest interaction and service communication, emphasizing the need for a specific vocabulary and contextual, practice-oriented learning for guests. Despite a strong recognition of the demands of the professional language, students report continuing challenges related to vocabulary mastery, pronunciation and communication confidence, revealing a gap between the goals and actual preparations. The study contributes to ESP research by extending the accommodation-oriented needs analysis to students of the English Study Programme and highlighting the coexistence of professional consciousness and communication constraints. The results support the development of English instruction based on performance, based on scenarios, in vocational contexts.